Pemetaan Kompetensi untuk Pengembangan Penilaian Kinerja Berbasis Kompetensi di Unit Kerja Perawatan Intensif (ICU) Rumah Sakit Adi Husada Kapasari Surabaya - Widodo Dwi Utomo; Suryanto Suryanto; Falih Suaedi (Universitas Negeri Surabaya, 2018)
Adi Husada Kapasari Hospital is one of the companies that is engaged in the field of health care services which prioritize the development of human resources to achieve strategic objectives of the company. Relating to the company's priorities, Adi Husada Kapasari Hospital require a good performance appraisal systems, including for employee of Intensive Care Unit (ICU). The Development of a competency-based performance appraisal is one of the alternatives to evaluate employees performance objectively. Competency-based performance appraisal performance appraisal is based on the competencies that is needed in order to make the job can be implemented effectively which the criterias of the assessment obtained from the job descriptions and the job specifications. In other words, a competency-based performance appraisal want to connect whether the competency of an employee can meet the demands of a position or a job, so it can be performed well. The Competency mapping which conducted in the job analysis successfully identified a number of competencies of each position in the intensive care unit, which divided into core competencies, general competencies , and specific competencies. The combination of three kinds of competence is referred to as the competency profile. The Competency profile of each position becomes the performance assessment criteria that will be used to evaluate performance each of the incumbent.